The More Things Change, the More They Stay the Same: A Study to Evaluate Compliance With Inclusion and Assessment of Women and Minorities in Randomized Controlled Trials. (April 2018) - Geller, Stacie E.; Koch, Abigail R.; Roesch, Pamela; Filut, Amarette; Hallgren, Emily; Carnes, Molly
Abstract : Purpose: The National Institutes of Health (NIH) Revitalization Act of 1993 requires NIH-funded clinical trials to include women and minorities as participants and assess outcomes by sex and race or ethnicity. The objective of this study was to investigate current levels of compliance with these guidelines for inclusion, analysis, and reporting in NIH-funded randomized controlled trials (RCTs) and compare the results with those from 2009 and 2004, which the authors reported previously. Method: The authors identified 782 RCTs published in 14 leading U.S. medical journals in 2015 with a PubMed search. Of those, 142 were the primary report of an NIH-funded RCT, conducted in the United States, and eligible for analysis. The authors reviewed abstract, text, and tables of each eligible study as well as any follow-up published commentary to determine compliance with NIH guidelines. Results: Thirty-five studies limited enrollment to one sex. The median enrollment of women in the remaining 107 studies was 46%, but 16 (15.0%) enrolled less than 30% women. Twenty-eight of the 107 (26%) reported at least one outcome by sex or explicitly included sex as a covariate in statistical analysis. Of the 142 studies, 19 (13.4%) analyzed or reported outcomes by race or ethnicity. There were no statistically significant changes in inclusion, analysis, or reporting by sex, race, or ethnicity compared with the previous studies. Conclusions: NIH policies have not resulted in significant increases in reporting results by sex, race, or ethnicity. The authors recommend strong journal policies to increase compliance with NIH policies. Abstract : Supplemental Digital Content is available in the text.